Beyond the Turtle Approach: Women in the Public Sector. (6th May 2020) - Neal, Sue M.; Gherardi, Michelle R.; Olejarski, Amanda M.
Abstract: Equity issues persist in defining public sector women as in need of accommodation, including during times of child‐rearing or caregiving. The authors argue instead that viewing the fullness of a woman ' s existence should empower others to see broad life experiences as a benefit to be fostered. Public service organizations and the academy should build policies and systems that recognize this value and work to cultivate, rather than accommodate. While women have historically taken the turtle approach—that is, keep your head down—the #MeToo movement has morphed women into strong bison, standing shoulder to shoulder. The authors advocate for more inclusive and supportive mentoring relationships to move into a new era—the pigeon era. In public administration, this manifests as providing holistic support and intentional mentorships throughout the arc of women ' s careers and institutional policy changes that support the unique value of women in the public sector and the academy.